Determination of acid dissociation constants, enthalpy, entropy andGibbs free energy of the baricitinib by the UV-metric and pH-metricanalysis - Meloun, Milan; Pfeiferová, Aneta; Javůrek, Milan; Pekárek, Tomáš (My University, 2020)
Baricitinib is a drug used for the treatment of rheumatoid arthritis. It is a selective and reversible inhibitor of Janus kinases 1 and 2, which play an important role in signalling the pro-inflammatory pathway activated in autoimmune disorders such as rheumatoid arthritis. The pH-spectrophotometric and pH-potentiometric titrations allowed the measurement of three or four successive dissociation constants of Baricitinib. Baricitinib neutral LH2 molecule was able to protonate into two soluble cations LH42+, LH3+ and dissociate into two soluble anions LH− and L2- in pure water. The graph of molar absorption coefficients of differently protonated species versus wavelength indicated that the spectra εL, εLH, εLH2 were the nearly the same for these species and that the spectra εLH4 and εLH3 were also similar. In the pH range from 2–13, four pKa´s of spectra analysis were reliably estimated by REACTLAB at I =0.0020 mol. dm-3 values pKTa1 = 3.07, pKTa2 = 3.87, pKTa3 = 6.27, pKTa4 = 12.78 at 25 °C and pKTa1 = 3.00, pKTa2 = 3.79, pKTa3 = 6.12, pKTa4 = 12.75 at 37 °C. Potentiometric pH-titration analysis for a higher concentration of 1 × 10-3 mol. dm-3 estimated with ESAB at I =0.0001 mol. dm-3 values pKTa1 = 3.69, pKTa2 = 3.81, pKTa3 = 4.73 at 25 °C and pKTa1 = 3.62, pKTa2 = 3.73, pKTa3 = 4.43 at 37 °C. Molar enthalpy ΔH°, molar entropy ΔS° and Gibbs free energy ΔG° were calculated from the spectra using a dependence ln K to 1/T.
Stanovení kyselých disociačních konstant, entalpie, entropie a Gibbsovy volné energie baricitinibu UV-metrickou a pH-metrickou analýzou
Keywords: dissociation constants; baricitinib; spectrophotometric titration; pH-titration; REACTLAB; SQUAD84; ESAB; disociační konstanty; baricitinib; spektrofotometrická titrace; titrace pH; REACTLAB; SQUAD84; ESAB